PELATIHAN DASAR BACKEND DEVELOPMENT FRAMEWORK LARAVEL 12 MELALUI WEBINAR DAN WORKSHOP - Muhammad Imam Najib; Muhammad Rayyan Ghifari; Muhammad Lutfi Yatna; Dzaki Fawwaz Aryadi; Jumail; Yana Adharani; Rully Mujiastuti; Sitti Nurbaya Ambo (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
In the era of digital transformation, backend development skills are crucial for students, especially in the field of information technology. This community service activity aimed to provide students with fundamental understanding and skills in building REST APIs using Laravel 12, a modern PHP framework widely used in the industry. The activity, titled “Building Your First Backend Project With Laravel 12”, consisted of two sessions: a webinar that introduced the MVC architecture, Laravel installation, and REST API structure, and a hands-on workshop focusing on configuring the project, database connection, and implementing CRUD endpoints. The event was conducted online and attended by 20 participants from various institutions. Evaluation was carried out through pre-test and post-test assessments, as well as a feedback questionnaire. The results showed an increase in participants’ understanding of backend development using Laravel. Most participants expressed satisfaction with the materials and the presenters. This activity is expected to serve as a model for